Strengthening Local Food Security Through Analysis of The Impact of The Pumped Irrigation Program In Lebak Regency - Dedi Wahyudin; Riswanda Riswanda; Riny Handayani (Green Publisher Indonesia, 2025)
This study aims to evaluate the implementation of the Pumped Irrigation Program in Lebak Regency, Banten, and its impact on food security. The agricultural sector in Lebak faces significant challenges, including suboptimal productivity and high dependence on rainfed land, which threatens regional food security. This study uses an evaluative qualitative approach with a six-criteria framework from William N. Dunn (effectiveness, efficiency, adequacy, equity, responsiveness, and accuracy) to conduct a comprehensive analysis. Data were collected through in-depth interviews with key stakeholders, participatory observations, as well as analysis of program documents and statistical data. The results revealed a significant